Dominant psychoactive drugs in the Central European region: A wastewater study. (October 2016) - Mackuľak, Tomáš; Bodík, Igor; Hasan, Jamal; Grabic, Roman; Golovko, Oksana; Vojs-Staňová, Andrea; Gál, Miroslav; Naumowicz, Monika; Tichý, Jozef; Brandeburová, Paula; Híveš, Ján
Highlights: We analyzed 26 psychoactive wastewater compounds in 17 various Slovak and Czech cities. More than 10% of the Slovak and Czech population (1.5 million inhabitants) were included in the study. High consumption of cheap drugs like methamphetamine was found. We revealed significant local differences in the drug cocaine and marijuana use pattern among the cities. A spa town – a major source of wastewater load with psychopharmaceuticals. Abstract: The aim of this study was to analyze 26 various illicit drugs, psychopharmaceuticals and metabolites thereof in sewer from 17 selected wastewater treatment plants (WWTPs) in the Slovak and Czech Republics. Urinary bio-markers used were analyzed using liquid chromatography coupled with the tandem mass spectrometry (LC–MS/MS). We then compared our results with data obtained in other parts of Europe and the world. The present study shows that the Slovak and Czech Republics have one of the highest methamphetamine consumption rates in Europe. Within Slovakia, the highest level of methamphetamine consumption was found in Dunajská Streda with the mean specific load of the drug in sewage being up to 479 mg/day/1000 inhabitants; the next highest load was detected in Trnava (354 mg/day/1000 inhabitants). The methamphetamine, ecstasy and cannabis consumptions in our study were comparable to those found in other European cities, whereas cocaine consumption was lower. Among all of the studied psychopharmaceuticals, tramadol and venlafaxine were represented in the highest concentrations. The highest mean specific load of tramadol was detected in the spa town of Piešťany (371 mg/day/1000 inhabitants) and Košice (372 mg/day/1000 inhabitants), while the highest mean loads of venlafaxine were recorded for the towns of Trenčín (230 mg/day/1000 inhabitants) and Piešťany (108 mg/day/1000 inhabitants).